A Comparative Analysis of the Predictive Abilities of Economic Complexity Metrics Using International Trade Network. (13th February 2018) - Liao, Hao; Vidmer, Alexandre
Abstract : The complex networks approach has proven to be an effective tool to understand and predict the evolution of a wide range of complex systems. In this work, we consider the network representing the exchange of goods between countries: the international trade network. According to the type of goods they export, the complex networks approach allows inferring which countries will have a bigger growth compared to others. The aim of this work is to study three different methods characterizing the complex networks and study their behaviour on two main topics. Can the method predict the economic evolution of a country? What happens to those methods when we merge the economies?